Asociación de infección de herida quirúrgica y el egreso por defunción en el HGZ MF No. 12 durante el periodo 01 de enero 2019 al 31 de diciembre de 2021 - García Pérez, Nury Lissett (Universidad Michoacana de San Nicolas de Hidalgo, 2025)
Introduction: In wound infection surgery, risk factors must be identified, considering the interventions performed, to improve preventive actions such as reducing mortality. Objective: Determine the association between the presence of surgical wound infection and discharge due to death in the HGZ MF No. 12, IMSS. Material and methods: An observational, retrospective, descriptive study was carried out at the HGZ MF No. 12, IMSS, with a discretionary non-probabilistic sampling technique in 128 patients with surgical wound infection hospitalized between January 1, 2019 and December 31, 2021. Statistical analysis was performed with measures of frequency, central tendency, standard deviation, logistic regression and Mann Whitney U. Results: The total number of patients studied (n=128), 56.3% male, 43.8% female, mean age 46.9 years, 86.7% without previous comorbidity, with mean hospital stay of 10.55 days, most frequently attended service was general surgery 49.2%, clean-contaminated wound 70.3%, type of deep infection 84.4%, association between hospital discharge due to death with days of hospital stay (p=0.046), discharge due to death with type 2 diabetes (p=0.048). Registration number of the IMSS Local Health Ethics and Research Committee: R-2023-1603-003. Conclusions: The days of hospital stay increase the risk of death. Type 2 diabetes increases the probability of dying by 13 times in the event of a surgical wound infection.

Introducción: En la infección de herida quirúrgica, se deben identificar los factores de riesgo, considerando las intervenciones realizadas, para mejorar las acciones preventivas como reducir la mortalidad. Objetivo: Determinar la asociación entre la presencia de infección de herida quirúrgica y el egreso por defunción en el HGZ MF No. 12, IMSS. Material y métodos: Se realizó un estudio observacional, retrospectivo, descriptivo, en el HGZ MF No. 12, IMSS, con técnica de muestreo no probabilístico discrecional en 128 pacientes con infección de herida quirúrgica hospitalizados entre el 01 de enero del 2019 al 31 de diciembre del 2021. El análisis estadístico se realizó con medidas de frecuencia, tendencia central, desviación estándar, regresión logística y U de Mann Whitney. Resultados: El total de pacientes estudiados (n=128), un 56.3% masculino, 43.8% femenino, edad media 46.9 años, 86.7% sin comorbilidad previa, con estancia intrahospitalaria media de 10.55 días, servicio de atención con mayor frecuencia fue cirugía general 49.2%, herida limpia-contaminada 70.3%, tipo de infección profunda 84.4%, asociación entre egreso hospitalario por defunción con días de estancia intrahospitalaria (p=0.046), egreso por defunción con diabetes tipo 2 (p=0.048). Número de Registro del Comité Local de Ética e investigación en Salud del IMSS: R-2023-1603-003. Conclusiones: Los días de estancia intrahospitalaria aumentan el riesgo de defunción. La diabetes tipo 2, aumenta la probabilidad 13 veces el riesgo de fallecer en caso de presentar infección de herida quirúrgica.
Facultad de Ciencias Médicas y Biológicas. Especialidad en Medicina Familiar
Keywords: info:eu-repo/classification/cti/3; FCMB-E-2025-0079; Infección; Herida quirúrgica; Mortalidad; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/19072